2013
DOI: 10.1128/mcb.00238-13
|View full text |Cite|
|
Sign up to set email alerts
|

Glypican 1 Stimulates S Phase Entry and DNA Replication in Human Glioma Cells and Normal Astrocytes

Abstract: c Malignant gliomas are highly lethal neoplasms with limited treatment options. We previously found that the heparan sulfate proteoglycan glypican 1 (GPC1) is universally and highly expressed in human gliomas. In this study, we investigated the biological activity of GPC1 expression in both human glioma cells and normal astrocytes in vitro. Expression of GPC1 inactivates the G 1 /S checkpoint and strongly stimulates DNA replication. Constitutive expression of GPC1 causes DNA rereplication and DNA damage, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…It can act as a co-receptor/modulator for many angiogenic factors including members of the FGF and VEGF growth factor families [40, 4447]. Several studies also have shown that glypican-1 can stimulate cell cycle progression in endothelial cells [43, 48]. In this work, we show that glypican-1 is lost in the blood vessels of skin samples from human patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…It can act as a co-receptor/modulator for many angiogenic factors including members of the FGF and VEGF growth factor families [40, 4447]. Several studies also have shown that glypican-1 can stimulate cell cycle progression in endothelial cells [43, 48]. In this work, we show that glypican-1 is lost in the blood vessels of skin samples from human patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 58%
“…A hallmark of gliomas is vigorous angiogenic response to the tumor that drives neovascularization through multiple mechanisms [3033]. Glypican-1 has a key role in the growth, metastasis and angiogenic properties of gliomas [4043]. In addition, glypican-1 is the most prevalent member of the glypican family expressed in endothelial cells and the vascular system [44].…”
Section: Introductionmentioning
confidence: 99%
“…GPC1 is a member of the glypican family, which comprises HSPGs, linked via a glycosyl-phosphatidylinositol (GPI) anchor to the extracellular membrane. GPC1 functions in angiogenesis, cell-cycle promotion and mitogenic growth in cancer cells ( Qiao et al , 2008 , 2012 , 2013 ). Other reports have shown that GPC1 is essential for mitogenic signalling promoted by FGF2 and HB-EGF, and plays a crucial role in neoplastic transformation and tumour progression in some cancers ( Kleeff et al , 1998 , 1999 ; Gengrinovitch et al , 1999 ; Matsuda et al , 2001 ; Ding et al , 2005 ; Su et al , 2006 ; Aikawa et al , 2008 ; Okolicsanyi et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PI3K/Akt/mTOR is a critical regulatory pathway in autophagy response ( Takeuchi et al, 2005 ; Guertin and Sabatini, 2007 ). Recent study revealed that PI3K/Akt/mTOR signal pathway would be commonly activated in human glioma cells ( Qiao et al, 2013 ; Shin et al, 2013 ; Xu et al, 2013 ). To further investigate the possible mechanism involved in this process, we studied the effect of EMAP II on P13K, Akt, and mTOR signal molecules.…”
Section: Discussionmentioning
confidence: 99%